Hypothermic machine perfusion in liver transplantation. (October 2020) - Karangwa, S.; Panayotova, G.; Dutkowski, P.; Porte, R.J.; Guarrera, J.V.; Schlegel, A.
Abstract: Dynamic preservation strategies are a promising option to improve graft quality before transplantation, and to extend preservation time for either logistic or treatment reasons. In contrast to normothermic oxygenated perfusion, which intends to mimic physiological conditions in the human body, with subsequent clinical application for up to 24 hrs, hypothermic perfusion is mainly used for a relatively short period with protection of mitochondria and subsequent reduction of oxidative injury upon implantation. The results from two randomized controlled trials, where recruitment has finished are expected this year. Both ex situ perfusion techniques are increasingly applied in clinical transplantation including recent reports on viability assessment, which could open the door for an increased liver utilization in the future. Highlights: Hypothermic liver perfusion (HMP) improves liver function and reduces complications after liver transplantation. Protection of the biliary tree was described as one main benefit of hypothermic liver perfusion. Hypothermic perfusion induces a switch of the mitochondrial metabolic status and reloads cellular energy before implantation. Viability testing during HMP is feasible using mitochondrial markers (FMN), released from mitochondrial complex I. Perfusate FMN concentrations predict overall survival and complications after implantation. Clinical validation is ongoing.